Effects of Patient Educational Programs on the Headache Caused by Spinal Anesthesia - Reza Aberomand; Ali Ravari; Tayebeh Mirzaei; Mohsen Savaie (Mashhad University of Medical Sciences, 2015)
Background: Headache is the most common complication caused by spinal anesthesia. Systematic educational programs about conservative treatments could be effective in the reduction of headache after spinal anesthesiz. Aim: This study aimed to evaluate the effects of training programs on the headache of patients after spinal anesthesia. Method: This empirical study was conducted on 120 patients within the age range of 16-40 years who were candidates for general, orthopedic and urology surgeries in Dr. Shahidzadeh Hospital of Behbahan, Iran in 2015. Patients were randomly divided into two groups of intervention and control. Scheduled training was provided for the intervention group, and the control group received routine training. Intensity of headache was recorded using the visual analogue scale (VAS). Data analysis was performed in SPSS V.14 using Chi-square and independent T-test. Results: In this study, Chi-square test showed a statistically significant difference between the groups in terms of incidence and time of occurrence of headaches. In total, eight patients (25.8%) in the intervention group and 23 patients (74.2%) in the control group had headaches (P=0.001). In the first 48 hours after anesthesia, all patients in the intervention group and 11 patients (47.8%) in the control group had headaches (P=0.03). Moreover, independent T-test revealed a significant difference between the mean of pain intensity in patients of the intervention (5.0±1.8) and control groups (7.1±2.1) (P=0.01). Implications for Practice: According to the results of this study, systematic education of patients could effectively reduce the occurrence and intensity of headaches after spinal anesthesia. Therefore, it is recommended that patient training be included in the preoperative preparation program in order to prevent headaches after surgery.